Penatalaksanaan Emesis Gravidarum Buah Pisang Ambon di Puskesmas Rajabasa Indah Bandar Lampung Tahun 2023 - Ristiyana, Septi; Meisari, Putri; Destri, Yuhelva; Rinjani, Margareta (Penerbit Goodwood, 2024)
Purpose: The student is able to apply midwifery care to Mrs. A, aged 24, G1P0A0, at 9 weeks and 2 days of pregnancy, with the management of Emesis Gravidarum using Ambon bananas at the Rajabasa Indah Health Center in 2023. Methods: The case report used was a descriptive report with a case study approach (case review study). A case study was conducted by investigating a problem using a case consisting of a single unit. Results: The results of this study showed a difference in the average frequency of nausea and vomiting before and after Ambon Banana intervention. The bivariate results show a p-value of 0.000 and an ? value of 0.05, indicating the effectiveness of the Ambon banana on the frequency of Emesis Gravidarum in pregnant women during the first trimester. Limitations: The study focused on a single case or a small sample size, which may not be representative of the broader population of pregnant women experiencing Emesis Gravidarum. Contributions: This article highlights a natural, easily accessible remedy, Ambon bananas, for managing Emesis Gravidarum, offering a low-cost alternative for pregnant women suffering from nausea and vomiting.